Preschoolers' perceptions of gendered toy commercials in the US. Issue 2 (3rd April 2017) - Zimmermann, Laura K.
Abstract: While much is known about the gender stereotypic nature of child-directed ads, little work examining how preschoolers perceive these gendered messages has been done. To this end, interviews with 60 preschool-aged children from childcare centers in Northern Virginia were conducted. Children were shown five toy advertisements (two male-targeted, two female-targeted, one neutral) and asked about gender classification as well as commercial preferences, which were assessed verbally and behaviorally. Results revealed stereotype flexibility as well as rigidity. Some level of flexibility was seen in all areas. Rigidity was most pronounced in the children's emotional response to the ads and in their choice of favorite commercial. Moreover, in boys, adherence to stereotypes was more prominent and increased with age. Preschoolers' perceptions of gendered toy commercials are multifaceted and more work is needed to understand the influences that shape them.